1998
DOI: 10.1093/jn/128.6.947
|View full text |Cite
|
Sign up to set email alerts
|

Weaning and the Weanling Diet Influence the Villous Height and Crypt Depth in the Small Intestine of Pigs and Alter the Concentrations of Short-Chain Fatty Acids in the Large Intestine and Blood

Abstract: Effects of weaning pigs to different diets have been investigated in terms of the changes in the small intestinal morphology, and in the absorption of short-chain fatty acids (SCFA) and sodium from the large intestine. One piglet from each of six litters containing nine pigs was sampled on the day of weaning; the other eight piglets were divided into four equal groups and fed different diets as follows: unweaned, weanling diet, or sow's milk at high or low level. Four and seven days after weaning, measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
106
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(120 citation statements)
references
References 25 publications
14
106
0
Order By: Relevance
“…Findings of shorter crypts on d 3 post-weaning in piglets on the low feed intake (trial 2) concur with the results of Pluske et al [34] showing, at 5 d post-weaning, shorter crypts in piglets fed at MEm than in those fed 2.5 times MEm. Furthermore, findings that shorter crypts are found in pigs weaned into a "clean" environment compared to pigs weaned into a "conventional" environment [30,44], suggest that the rate of epithelial renewal a marginal effect of weaning on crypt depth was found in our studies in agreement with the findings of Spreeuwenberg et al [42], whereas a transient decrease on d 2 postweaning was found by McCracken et al [28] and van Beers-Schreurs et al [47]. Crypt depth is dependent on several factors including the level of energy intake.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Findings of shorter crypts on d 3 post-weaning in piglets on the low feed intake (trial 2) concur with the results of Pluske et al [34] showing, at 5 d post-weaning, shorter crypts in piglets fed at MEm than in those fed 2.5 times MEm. Furthermore, findings that shorter crypts are found in pigs weaned into a "clean" environment compared to pigs weaned into a "conventional" environment [30,44], suggest that the rate of epithelial renewal a marginal effect of weaning on crypt depth was found in our studies in agreement with the findings of Spreeuwenberg et al [42], whereas a transient decrease on d 2 postweaning was found by McCracken et al [28] and van Beers-Schreurs et al [47]. Crypt depth is dependent on several factors including the level of energy intake.…”
Section: Discussionsupporting
confidence: 92%
“…These alterations are assumed to impair the ability of the small intestine to digest and absorb nutrients and to predispose the weanling piglet to malabsorption and diarrhoea [27,46]. Although several factors may account for these morphological changes, there is increasing evidence that the level of feed intake is an important factor [27,34,47]. However, less is known on the effects of weaning on the spatial and temporal changes in intestinal morphology and on the speed of recovery.…”
Section: Introductionmentioning
confidence: 99%
“…D-Xylose has been widely used to determine absorptive capacity (Hammon and Blum, 1997). Serum D-xylose concentration decreased, indicating that weaning reduced the intestinal absorptive capacity, as reported in other studies (van Beers-Schreurs et al, 1998;Gu et al, 2002). Galactose is a unique dietary sugar in that its exclusive source is milk lactose, and it provides approximately 20% of the total caloric intake in exclusively breastfed infants (Coss-Bu et al, 2009).…”
Section: Fig 7 Kegg Pathways Linked Together Manuallymentioning
confidence: 83%
“…Large amounts of lactose, free and protein-bound amino acids, saturated fatty acids, and unsaturated fatty acids are present in sow's milk (Wu and Knabe, 1994;Mountzouris et al, 1999;van den Borne et al, 2007). After weaning, the piglets ingested complete feed rich in nitrogen compounds with small amounts of fat and carbohydrates (Gu and Li, 2003;Petrovič et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Stimulating solid feed intake before weaning is proposed as a strategy to mitigate the abrupt transition between maternal milk supply and creep feed consumption, with an expected positive effect on the rate of weight gain and the prevention of intestinal disorders (Van Beers-Schreurs et al, 1998;Berkeveld et al, 2007). In assays studying effects of IS on conventional porcine breeds, access to the sow was drastically limited during 10 or 12 h from the onset of the treatment (Berkeveld et al, 2007 andKuller et al, 2007).…”
Section: Discussionmentioning
confidence: 99%